Analisis Putusan Mahkamah Konstitusi Nomor 62/PUU-XXII/2024 Tentang Penghapusan Presidential Threshold Perspektif Siyasah Qadhaiyyah - Munawir Harahap; Mhd. Yadi Harahap (LPPM Institut Pendidikan Nusantara Global, 2025)
The Constitutional Court Decision Number 62/PUU-XXII/2024, which annulled the presidential threshold provision in Article 222 of the Election Law, represents a significant legal event in Indonesian constitutional law. This study aims to analyze the Court's legal reasoning and its alignment with the principles of Islamic justice through the lens of Siyasah Qadhaiyyah. Employing a normative legal method with a statutory approach, case law approach, and comparative approach, the study draws upon primary legal sources and literature on fiqh siyasah. The analytical approach applied in this study is descriptive-qualitative, emphasizing a comprehensive understanding of the content and context of the data. The findings reveal that the Court deemed the threshold unconstitutional and in conflict with the principle of popular sovereignty. From the perspective of Islamic law, this decision reflects the values of al-‘adl (justice), al-maslahah (public interest), and al-musawah (equality), and illustrates the Court's role as a modern embodiment of wilayah al-mazalim.